2016
DOI: 10.1016/j.bone.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral properties in growing Col1a2+/G610C mice, an animal model of osteogenesis imperfecta

Abstract: The Col1a2+/G610C knock-in mouse, models osteogenesis imperfecta in a large old order Amish family (OOA) with type IV OI, caused by a G-to-T transversion at nucleotide 2098, which alters the gly-610 codon in the triple-helical domain of the α2(I) chain of type I collagen. Mineral and matrix properties of the long bones and vertebrae of male Col1a2+/G610C and their wild-type controls (Col1a2+/+), were characterized to gain insight into the role of α2-chain collagen mutations in mineralization. Additionally, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 47 publications
7
26
0
Order By: Relevance
“…Further, FTIR studies of different OI mouse models with dominant OI mutations (G610C and Mov13) and Lrp5 HBM showed no change in the abnormal mineral to matrix ratio seen in OI bone, consistent with lack of improvement in bone quality. (45, 51) Similar results were seen in another mouse model (Brtl) when juvenile mice were treated for 2 or 5 weeks with Sclerostin antibody. There was no improvement in brittleness nor an effect on the estimated elastic modulus.…”
Section: Osteogenesis Imperfectasupporting
confidence: 72%
“…Further, FTIR studies of different OI mouse models with dominant OI mutations (G610C and Mov13) and Lrp5 HBM showed no change in the abnormal mineral to matrix ratio seen in OI bone, consistent with lack of improvement in bone quality. (45, 51) Similar results were seen in another mouse model (Brtl) when juvenile mice were treated for 2 or 5 weeks with Sclerostin antibody. There was no improvement in brittleness nor an effect on the estimated elastic modulus.…”
Section: Osteogenesis Imperfectasupporting
confidence: 72%
“…Col1a2 tm1.1Mcbr mice showed reduced bone mass and cortical thickness as well as decreased biomechanical properties [43,44]. In the same study, an increase in mineral-to-collagen ratio was observed, indicating more brittleness in Col1a2 tm1.1Mcbr bones [43,44].…”
Section: Genetic Causes and Mechanisms Of Osteogenesis Imperfectamentioning
confidence: 95%
“…Col1a2 tm1.1Mcbr mice showed reduced bone mass and cortical thickness as well as decreased biomechanical properties [43,44]. In the same study, an increase in mineral-to-collagen ratio was observed, indicating more brittleness in Col1a2 tm1.1Mcbr bones [43,44]. Similar to the Aga2 +/− model, increased expression of Ddit3 and Hsp47 was observed in Col1a2 tm1.1Mcbr mice, indicating that high ER stress and UPR activation may potentially account for osteoblast dysfunction in mutant mice [45].…”
Section: Genetic Causes and Mechanisms Of Osteogenesis Imperfectamentioning
confidence: 99%
“…Using a Spectrum 300 (Perkin Elmer, CT, USA) infrared spectrometer and microscope, images were acquired at 3 different trabecular and cortical sites for each bone as previously described. (22)…”
Section: Methodsmentioning
confidence: 99%